In situ observation of catalytic CeO2-nanocube (100) surface with carbon contamination by environmental TEM: a model for soot combustion. (16th October 2020) - Ozawa, Masakuni; Higuchi, Kimitaka; Nakamura, Keita; Hattori, Masatomo; Ohara, Satoshi; Arai, Shigeo
Abstract: An environmental transmission electron microscopy (ETEM) was applied to the in situ observation of carbon contamination removal reaction on (100) crystal plane of catalytic CeO2 nanocubes. The distance between the surface of CeO2 and carbon layer (width) was quantitatively measured versus time at eleven points on three CeO2 nanocubes by observation at an oxygen pressure of 3.0 × 10 −1 Pa at 400 °C. The carbon contamination removal rate in the time range of 100 to 460 s was 0.01 ± 0.002 nm s −1, not depending on the place. However, in the later stage, the rates of 0.057 ± 0.01 nm s −1 and 0.24 ± 0.02 nm s −1 were obtained for carbon contamination of different areas in the specimen even if the same crystal plane (100) was in contact with carbon. Carbon on the crystal surface in the inner area of the CeO2 aggregate was eliminated more quickly than contamination in the outer area. The result means that the local-environmental influence in nanoparticle aggregates is taken into account in a heterogeneous catalytic reaction as well as contamination reduction using ETEM.